Accessibility to schooling in South African rural areas - Narcy, Deisy (Department of Civil Engineering, 2021)
In developing countries rural communities are normally geographically isolated contributing to both poverty levels and the deficiency in the participation of social and economic activities. Accessibility to education constitutes one of the primordial links between the economic growth of a country and the development of high skilled population. Given South Africa's unique history, divisions throughout the landscape incapacitate inhabitants of rural communities in reaching opportunities and services, therefore, aggravating issues related to social exclusion and inequality. This study aims to determine accessibility levels in South African rural regions by looking at different aspects that entangle the theory behind it, specifically: the zone attractiveness and impedance. With that in mind, the investigations carried out are firstly directed towards accessibility at the provincial level and thereafter a focus area is determined. At the provincial level, it was found that the Northern Cape presented the greatest disadvantages. However, given insufficient resources and data related to this province, the Cape Winelands Municipality District was chosen as the area to extend the investigations. When assessing the focus area, the study deployed a GIS-based analysis wherein potential and real accessibility were determined. Initially using the gravity measure, and subsequently using a survey carried out in the region. The study has revealed that Stellenbosch and Robertson are the towns experiencing high accessibility levels. Notwithstanding, most principal towns still experience critically low accessibility indexes. The findings of this study can, therefore, be useful in indicating areas that need further studies or are experiencing disadvantages regarding accessibility.